2022
DOI: 10.3389/fonc.2021.670897
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Changes During Endocrine Therapy in Breast Cancer Patients: The Results of a 5-Year Real-World Retrospective Analysis

Abstract: BackgroundThe aim of this study was to investigate the status of serum lipids during endocrine therapy.MethodsWe retrospectively analysed lipid profiles during the 5-year treatment of 1487 consecutive postoperative BC patients. Lipid parameters included triglycerides (TG), total cholesterol (TC), low-density lipoprotein (LDL-C) and high-density lipoprotein (HDL-C). Those biomarkers were measured at baseline and 1, 2, 3, 4 and 5 years following the initiation of endocrine therapy.ResultsFor premenopausal BC pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…[ 24 ] However, in BC endocrine therapy, Tamoxifen reduced TC and LDL-C levels. [ 15 ] Tamoxifen binds to microsomal antiestrogen binding sites with high affinity and inhibits cholesterol esterification at therapeutic doses. [ 16 ] On the basis that ET is beneficial to controlling serum lipid levels, but lipid-related components are the factors driving endocrine resistance, we wanted to explore whether serum lipids have good predictive indicators for early screening of endocrine resistance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 24 ] However, in BC endocrine therapy, Tamoxifen reduced TC and LDL-C levels. [ 15 ] Tamoxifen binds to microsomal antiestrogen binding sites with high affinity and inhibits cholesterol esterification at therapeutic doses. [ 16 ] On the basis that ET is beneficial to controlling serum lipid levels, but lipid-related components are the factors driving endocrine resistance, we wanted to explore whether serum lipids have good predictive indicators for early screening of endocrine resistance.…”
Section: Discussionmentioning
confidence: 99%
“…[ 13 , 14 ] In BC endocrine therapy, Tamoxifen reduced total cholesterol (TC) and low-density lipoprotein cholesterol (LDL-C) levels. [ 15 ] Tamoxifen binds with high affinity to the microsomal antiestrogen binding site and inhibits cholesterol esterification at therapeutic doses. [ 16 ] There have also been some reports of lipid metabolism involved in ET, lipid metabolism is involved in tamoxifen resistance and cholesterol metabolism plays a role in tamoxifen resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Our nding of no association with dyslipidemia in pre-and postmenopausal tamoxifen users is generally consistent with the existing literature. Studies suggest favorable lipid pro les, including decreased total cholesterol and low-density lipoprotein cholesterol and increased high-density lipoprotein cholesterol, for tamoxifen users in both premenopausal and postmenopausal BC survivors [31][32][33][34][35][36][37][38][39][40][41][42]. In contrast, prior research frequently reports no signi cant changes in lipid pro les with AI use [19,34,35,41,43,44].…”
Section: Discussionmentioning
confidence: 99%
“…Studies suggest favorable lipid pro les, including decreased total cholesterol and low-density lipoprotein cholesterol and increased high-density lipoprotein cholesterol, for tamoxifen users in both premenopausal and postmenopausal BC survivors [31][32][33][34][35][36][37][38][39][40][41][42]. In contrast, prior research frequently reports no signi cant changes in lipid pro les with AI use [19,34,35,41,43,44]. Furthermore, studies investigating dyslipidemia as an outcome endpoint reported no association in BC survivors comparing AI to tamoxifen users [40,43].…”
Section: Discussionmentioning
confidence: 99%